Moray: Bridging an ancient culture of innovation with emerging pedagogies in engineering - Cornejo, Melanie Gisela (2018)
From its inception, Universidad de Ingeniería y Tecnología (UTEC) has functioned under the mandate of causing a disruptive effect in society by educating a new generation of holistic engineers bound to become empowered change agents. The university has recently embarked on a radical transformation of its educational model, in order to deliver this promise. A flexible curriculum provides students not only with a strong STHEAM backbone imparted in a student-centered active-learning format, but also exposes them to real engineering challenges and promotes the acquisition of professional skills from the onset. For this change to be implemented successfully, UTEC has decided to design and launch a Laboratory for Educational Innovation, called Moray. Conceived as an open platform, Moray sits at the intersection of physical and virtual spaces and is organized around flexible protocols that allow faculty, students, staff, and experts from top universities worldwide to work inter-disciplinarily and collaboratively, towards the enhancement of teaching and learning dynamics in higher education.